Semiconductor chip side packaging UV adhesive and preparation method thereof

By using side-filled semiconductor chip side-packaged UV glue in chip package, the problems of high cost of underfill and repair complexity are solved, achieving lower cost and simplified repair effects, while also suitable for high-density and miniaturized chip packages.

CN119912895APending Publication Date: 2025-05-02SHENZHEN SAPIENCE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510213273.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-25
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

In the existing chip packaging technology, underfill has problems such as high cost, complex processes, inability to repair and space limitations, making it difficult to meet the high requirements of 5G base stations and autonomous driving.

Method used

UV glue is encapsulated on the side of the semiconductor chip, and prepared by mixing raw materials such as epoxy resin, acrylate copolymer, modified spherical silica, etc., to form an adhesive that can cure under UV light and fill it on the sides of the IC and PCB.

Benefits of technology

It achieves lower production costs and simplified maintenance processes, reduces the risk of damage to PCBs, and has efficient UV light curing capabilities, suitable for miniaturization and high-density chip packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005286614370000131
    Figure BDA0005286614370000131
  • Figure BDA0005286614370000141
    Figure BDA0005286614370000141
Patent Text Reader

Abstract

The invention belongs to the technical field of filling adhesives, and discloses a semiconductor chip side packaging UV adhesive and a preparation method thereof. The semiconductor chip side surface packaging UV adhesive is prepared from the following raw materials in parts by mass: 10 to 20 parts of epoxy resin, 5 to 30 parts of acrylate copolymer, 30 to 80 parts of modified spherical silicon dioxide, 5 to 10 parts of negative thermal expansion material, 5 to 15 parts of epoxy diluent, 5 to 10 parts of nano silicon dioxide, 1 to 5 parts of fumed silica, 1 to 10 parts of photoinitiator, 0.1 to 2 parts of metal ion trapping agent and 0 to 0.5 part of stabilizer. The UV adhesive prepared by the invention keeps the reliability of mechanical properties, can easily realize the repair of a semiconductor chip after being heated to 210 DEG C, and has a relatively low CTE value which can be as low as lt; and the curing depth of 3mm can be reached only through single UV light curing of 9000 mJ / 10 s.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of filling adhesives, and in particular to a semiconductor chip side encapsulation UV adhesive and a preparation method thereof. Background Art

[0002] With the emergence of 5G base stations and autonomous driving technology, the reliability requirements of chip packaging will become increasingly higher. At present, the existing chip packaging technology is mainly bottom filling, which has the following main problems: (1) Relatively high cost: more adhesive materials are needed to completely fill the gap, and the process of complete filling is relatively complicated, requiring special equipment and technology, which will increase production costs and production time; (2) Cannot be repaired or reworked: Once the bottom filling is performed, if the module fails and needs to be repaired or reworked, the process of removing the filling glue will be more complicated. For example: the filling glue will be tightly combined with the ball grid array (BGA) and the printed circuit board (PCB), and it is easy to damage the components during the removal process, increasing the difficulty and cost of repair; (3) High space requirements: Since the space between the PCB and the BGA needs to be completely filled, for some miniaturized modules that are very sensitive to space, the bottom filling will be limited by space and cannot use the siphon effect to penetrate the filling, which may not meet the filling density requirements, thus affecting its actual application effect; (4) High energy consumption, the bottom filling is all thermally cured, requiring high temperature and 1 to 4 hours to be completely cured. Moreover, the packaging of large chips cannot adopt the bottom fill flip chip process at all. For example, in 5G millimeter wave applications, the bottom fill glue has an impact on the interconnection parasitic parameters of the broadband flip chip packaging.

[0003] Side filling is a simple, well-tested and cost-effective solution. Side filling was first proposed in the 1960s. Today, with the change in chip size and high requirements, especially for the two extreme sizes of chip packaging, side sealing has become a unique technical means. Side filling is a proven and cost-effective method to enhance the stability of the connection between the PCB and the BGA by applying adhesive on three sides of the integrated circuit (IC) and curing it. Tensile tests have shown that with side filling, the force that the module can withstand before it finally loosens can be increased by twice the original. However, as the size of small-size devices continues to shrink, for dynamic random access memory (DRAM) modules that are required to operate in extreme environments, how to come up with a viable side encapsulation adhesive is crucial to meet the above challenges. Summary of the invention

[0004] The purpose of the present invention is to provide a semiconductor chip side packaging UV glue and a preparation method thereof, so as to solve the problem that the existing adhesives cannot meet the performance requirements of the continuously shrinking device size in extreme environments.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The invention provides a semiconductor chip side encapsulation UV glue, which comprises the following raw materials in parts by mass: 10 to 20 parts of epoxy resin, 5 to 30 parts of acrylate copolymer, 30 to 80 parts of modified spherical silica, 5 to 10 parts of negative thermal expansion material, 5 to 15 parts of epoxy diluent, 5 to 10 parts of nano silica, 1 to 5 parts of fumed silica, 1 to 10 parts of photoinitiator, 0.1 to 2 parts of metal ion scavenger and 0 to 0.5 parts of stabilizer.

[0007] Preferably, in the semiconductor chip side encapsulation UV glue, the epoxy resin includes one or more of silicone alicyclic epoxy resin, alicyclic epoxy resin, bisphenol A epoxy resin, and bisphenol F epoxy resin.

[0008] Preferably, in the semiconductor chip side encapsulation UV glue, the acrylate copolymer is prepared by copolymerizing a first monomer, a second monomer, a third monomer and a fourth monomer;

[0009] The first monomer includes one or more of allyl acrylate, ethyl acrylate, butyl acrylate, isooctyl acrylate, ethyl methacrylate, allyl methacrylate, butyl methacrylate, and hydroxyethyl methacrylate;

[0010] The second monomer includes one or more of acrylic acid, methacrylic acid, acrylonitrile, styrene, 1,3-butadiene, acrylamide, and α-methylstyrene;

[0011] The third monomer includes one or more of dicyclopentadiene acrylate, isobornyl methacrylate, isobornyl acrylate, 2-phenoxyethyl acrylate, and 1,6-hexanediol diacrylate;

[0012] The fourth monomer includes one or more of glycidyl acrylate, glycidyl methacrylate, 2,3-epoxybutyl acrylate, allyl glycidyl ether, butyl glycidyl ether, and phenyl glycidyl ether;

[0013] The mass ratio of the first monomer, the second monomer, the third monomer and the fourth monomer is 5-8:0.5-2:1-1.5:1-3.

[0014] Preferably, in the semiconductor chip side encapsulation UV glue, the negative thermal expansion material includes zirconium tungstate and / or β-eucryptite;

[0015] The particle size of the negative thermal expansion material is 500nm-1μm.

[0016] Preferably, in the semiconductor chip side encapsulation UV glue, the epoxy diluent includes one or more of oxetane, vinyl ether, and allyl ether.

[0017] Preferably, in the semiconductor chip side encapsulation UV glue, the modified spherical silica is prepared by modifying spherical silica with a silane coupling agent, and the particle size of the spherical silica is 0.5 to 5 μm;

[0018] The particle size of the nano silicon dioxide is 10 to 20 nm;

[0019] The particle size of the fumed silica is less than 10 nm.

[0020] Preferably, in the semiconductor chip side encapsulation UV glue, the photoinitiator comprises a mixture of a first component and a second component;

[0021] The first component includes a mixture of castor oil polyol and 3,4-dihydroxy-3-cyclobutene-1,2-dione;

[0022] The second component includes one or more of the photoinitiator 184, isopropylthioxanthone ITX, sulfonium phosphate, iodonium phosphate, sulfonium antimonate ammonium salt, aziridine acrylate, and acridine.

[0023] Preferably, in the semiconductor chip side encapsulation UV glue, the stabilizer includes one or more of hydroquinone, p-methoxyphenol, p-benzoquinone, 2,6-di-tert-butyltoluene, and carbamate diol.

[0024] The present invention also provides a method for preparing a semiconductor chip side encapsulation UV glue, comprising the following steps:

[0025] (1) mixing a first monomer, a second monomer, a third monomer, a fourth monomer and an initiator to carry out a polymerization reaction to obtain an acrylate copolymer;

[0026] (2) mixing and grinding the modified spherical silica, the negative thermal expansion material, the nano-silica, the fumed silica, the metal ion scavenger, the stabilizer and part of the acrylic ester copolymer, and controlling the fineness of the mixed grinding to be within 20 μm to obtain a first mixed material;

[0027] (3) vacuum mixing and vacuum grinding the epoxy resin, the remaining acrylate copolymer, the epoxy diluent and the first mixed material in sequence, and controlling the fineness of the vacuum grinding to be within 10 μm to obtain a second mixed material;

[0028] (4) The second mixed material and the photoinitiator are mixed at a temperature of less than 25° C., and vacuum filtered to control the particle size within 5 μm, thereby obtaining a semiconductor chip side encapsulation UV adhesive.

[0029] Preferably, in the preparation method, the polymerization reaction in step (1) specifically comprises the following steps:

[0030] The first monomer is heated, and the second monomer and part of the initiator are added thereto to react to obtain a first intermediate; the first intermediate, the third monomer and the remaining initiator are mixed and reacted to obtain a second intermediate; the second intermediate and the fourth monomer are mixed and reacted to obtain an acrylate copolymer.

[0031] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0032] (1) When repairing the IC module, the bottom filling resin completely fills the space between the BGA and the PCB, so the removal process is relatively complicated and may cause damage to the PCB. Compared with the bottom filling, when the resin only needs to be coated on the sides of the IC and the PCB, the removal of the side filling resin is relatively simple, and the risk of damaging the PCB is low, which reduces the repair cost and difficulty to a certain extent. At the same time, the UV glue prepared in the present application can easily repair semiconductor chips by heating to 210°C while maintaining the reliability of mechanical properties. This is because the high reliability of the acrylate copolymer part and its thermal reversibility enable the network to decompose at high temperatures, making it easier to remove defective semiconductor chips; during the thermal rework process, this thermal reversible property makes the rework operation relatively easy, and the chip can be replaced without damaging surrounding components.

[0033] (2) The side-encapsulated UV glue provided by the present application has a unique delayed curing mechanism formula. It does not require thermal curing. A single UV light curing of 9000mJ / 10s can achieve a curing depth of 3mm, and a wavelength of LED 365nm can be used. Conventional UV glue can only achieve a curing depth of 1mm under the premise of a high proportion of fillers. This is because the UV glue prepared by the present application undergoes polycondensation due to light exposure on the surface to achieve preliminary curing, and the polymerization active species components therein can efficiently capture part of the energy in the ultraviolet light and temporarily store it. Then, through the action of 3,4-dihydroxy-3-cyclobutene-1,2-dione and castor oil polyol system, the energy is effectively transferred to the deep epoxy components through energy transfer and electron transfer, prompting them to undergo ring-opening polymerization, thereby achieving light curing of deeper UV glue and achieving the effect of increasing the curing depth under the same light range. In addition, the UV light transmittance is improved by modifying the surface of spherical silica.

[0034] (3) The side encapsulation UV glue provided in this application has a low CTE value, the lowest of which can reach <20ppm. This is due to the addition of negative thermal expansion materials (such as zirconium tungstate, β-eucryptite), which can reduce the thermal expansion coefficient through phase transformation under pressure and synergistically reduce the CTE value with modified spherical silica. DETAILED DESCRIPTION

[0035] The invention provides a semiconductor chip side encapsulation UV glue, which comprises the following raw materials in parts by mass: 10 to 20 parts of epoxy resin, 5 to 30 parts of acrylate copolymer, 30 to 80 parts of modified spherical silica, 5 to 10 parts of negative thermal expansion material, 5 to 15 parts of epoxy diluent, 5 to 10 parts of nano silica, 1 to 5 parts of fumed silica, 1 to 10 parts of photoinitiator, 0.1 to 2 parts of metal ion scavenger and 0 to 0.5 parts of stabilizer.

[0036] In the present invention, the epoxy resin preferably includes one or more of silicone alicyclic epoxy resin, alicyclic epoxy resin, bisphenol A epoxy resin, and bisphenol F epoxy resin, and further preferably includes silicone alicyclic epoxy resin, bisphenol A epoxy resin or bisphenol F epoxy resin, and more preferably is silicone alicyclic epoxy resin.

[0037] In the present invention, the source of the epoxy resin is not limited, and it can be obtained by a preparation method well known in the art or a commercially available product.

[0038] In the present invention, the weight percentage of the epoxy resin is preferably 12 to 20 parts, more preferably 15 to 20 parts, and even more preferably 16 parts.

[0039] In the present invention, the acrylic ester copolymer is preferably prepared by copolymerizing a first monomer, a second monomer, a third monomer and a fourth monomer.

[0040] In the present invention, the first monomer preferably includes one or more of allyl acrylate, ethyl acrylate, butyl acrylate, isooctyl acrylate, ethyl methacrylate, allyl methacrylate, butyl methacrylate, and hydroxyethyl methacrylate, and further preferably includes ethyl acrylate, butyl acrylate, ethyl methacrylate, allyl methacrylate, or butyl methacrylate, and more preferably includes ethyl acrylate or butyl acrylate.

[0041] In the present invention, the second monomer preferably includes one or more of acrylic acid, methacrylic acid, acrylonitrile, styrene, 1,3-butadiene, acrylamide, and α-methylstyrene, further preferably includes acrylonitrile, styrene, 1,3-butadiene or α-methylstyrene, and more preferably includes acrylonitrile or styrene.

[0042] In the present invention, the third monomer preferably includes one or more of dicyclopentadiene acrylate, isobornyl methacrylate, isobornyl acrylate, 2-phenoxyethyl acrylate, and 1,6-hexanediol diacrylate, and further preferably includes dicyclopentadiene acrylate, isobornyl methacrylate, isobornyl acrylate or 2-phenoxyethyl acrylate, and more preferably includes dicyclopentadiene acrylate or isobornyl methacrylate.

[0043] In the present invention, the fourth monomer preferably includes one or more of glycidyl acrylate, glycidyl methacrylate, 2,3-epoxybutyl acrylate, allyl glycidyl ether, butyl glycidyl ether, and phenyl glycidyl ether, and further preferably includes glycidyl acrylate, glycidyl methacrylate, 2,3-epoxybutyl acrylate or allyl glycidyl ether, and more preferably includes glycidyl methacrylate or allyl glycidyl ether.

[0044] In the present invention, the mass ratio of the first monomer, the second monomer, the third monomer and the fourth monomer is preferably 5-8:0.5-2:1-1.5:1-3, more preferably 5-7:0.5-1:1.2-1.5:2-3, and more preferably 5:0.5:1.5:3.

[0045] In the present invention, the mass fraction of the acrylic ester copolymer is preferably 10 to 28 parts, more preferably 16 to 25 parts, and even more preferably 20 parts.

[0046] In the present invention, the modified spherical silica is prepared by modifying spherical silica with a silane coupling agent, and the preparation method thereof preferably comprises the following steps:

[0047] The spherical silica is acid-leached, washed, and calcined in sequence to obtain pretreated silica;

[0048] The pH of the ethanol / water mixed solution is adjusted to 4-5, and epoxytriethoxysilane is added and mixed to obtain a silane solution;

[0049] The pretreated silica is mixed with a silane solution, ultrasonically dispersed, and then separated to obtain a crude product; the crude product is sequentially washed, dried, and heat-treated to obtain modified spherical silica.

[0050] In the present invention, the particle size of the spherical silica is preferably 0.5 to 5 μm, more preferably 1 to 4 μm, and even more preferably 2 μm.

[0051] In the present invention, the acid leaching agent is preferably sulfuric acid.

[0052] In the present invention, the concentration of sulfuric acid is preferably 0.1 to 1 mol / L, more preferably 0.5 to 1 mol / L, and more preferably 0.5 mol / L.

[0053] In the present invention, the agent for washing the spherical silica is preferably water.

[0054] In the present invention, the calcination temperature is preferably 300-500°C, more preferably 350-450°C, and more preferably 400°C; the calcination time is preferably 2-4h, more preferably 2.5-3.5h, and more preferably 3h.

[0055] In the present invention, in the ethanol / water mixed solution, the volume ratio of ethanol to water is preferably 8 to 10:1, more preferably 8.5 to 9.5:1, and more preferably 9:1.

[0056] In the present invention, the reagent for adjusting the pH to 4-5 is preferably acetic acid.

[0057] In the present invention, the time for adding epoxytriethoxysilane and mixing is preferably 0.5 to 2 hours, more preferably 0.8 to 1.5 hours, and more preferably 1 hour.

[0058] In the present invention, the mass concentration of the epoxytriethoxysilane in the silane solution is preferably 5 to 20%, more preferably 10 to 15%, and even more preferably 12%.

[0059] In the present invention, the solid-liquid mass ratio of the pretreated silicon dioxide to the silane solution is preferably 1:5-12, more preferably 1:8-11, and more preferably 1:10.

[0060] In the present invention, the conditions for ultrasonic dispersion include: the temperature is preferably 40-60°C, more preferably 45-55°C, more preferably 50°C; the time is preferably 2-4h, more preferably 2.5-3.5h, more preferably 3h.

[0061] In the present invention, the separation conditions preferably include: the rotation speed is preferably 3000-5000 rpm, more preferably 4000-5000 rpm, more preferably 5000 rpm; the time is preferably 5-20 min, more preferably 8-15 min, more preferably 10 min.

[0062] In the present invention, the reagent for washing the crude product is preferably ethanol; the number of washing is preferably 1 to 5 times, more preferably 2 to 4 times, and more preferably 3 times.

[0063] In the present invention, the drying conditions preferably include: the temperature is preferably 60-80°C, more preferably 70-80°C, more preferably 80°C; the time is preferably 6-12h, more preferably 8-12h, more preferably 10h.

[0064] In the present invention, the heat treatment conditions include: the temperature is preferably 100-120°C, more preferably 105-115°C, and more preferably 110°C; the time is preferably 1-2h, more preferably 1.2-1.8h, and more preferably 1.5h.

[0065] In the present invention, the mass fraction of the modified spherical silica is preferably 40 to 70 parts, more preferably 50 to 65 parts, and even more preferably 60 parts.

[0066] In the present invention, the negative thermal expansion material preferably includes zirconium tungstate and / or β-eucryptite, and more preferably zirconium tungstate.

[0067] In the present invention, the particle size of the negative thermal expansion material is preferably 500 nm to 1 μm, more preferably 800 nm to 1 μm, and even more preferably 1 μm.

[0068] In the present invention, the mass fraction of the negative thermal expansion material is preferably 6 to 10 parts, more preferably 6 to 8 parts, and even more preferably 8 parts.

[0069] In the present invention, the epoxy diluent preferably includes one or more of oxetane, vinyl ether, and allyl ether, and further preferably includes oxetane and / or vinyl ether, and more preferably is oxetane.

[0070] In the present invention, the weight percentage of the epoxy diluent is preferably 6 to 12 parts, more preferably 10 to 12 parts, and more preferably 12 parts.

[0071] In the present invention, the particle size of the nano-silicon dioxide is preferably 10 to 20 nm, more preferably 15 to 20 nm, and more preferably 20 nm.

[0072] In the present invention, the mass fraction of the nano-silicon dioxide is preferably 6 to 10 parts, more preferably 6 to 8 parts, and more preferably 8 parts.

[0073] In the present invention, the particle size of the fumed silica is preferably less than 10 nm.

[0074] In the present invention, the mass fraction of the fumed silica is preferably 2 to 5 parts, more preferably 3 to 5 parts, and even more preferably 4 parts.

[0075] In the present invention, the photoinitiator preferably comprises a mixture of a first component and a second component.

[0076] In the present invention, in the photoinitiator, the first component preferably includes a mixture of castor oil polyol and 3,4-dihydroxy-3-cyclobutene-1,2-dione.

[0077] In the present invention, in the photoinitiator, the second component preferably includes one or more of photoinitiator 184, isopropylthioxanthone ITX, sulfonium phosphate, iodonium phosphate, ammonium sulfonium antimonate, aziridine acrylate, and acridine, and further preferably includes photoinitiator 184, isopropylthioxanthone ITX, sulfonium phosphate or iodonium phosphate, and more preferably iodonium phosphate or ammonium sulfonium antimonate.

[0078] In the present invention, the mass fraction of the photoinitiator is preferably 3 to 8 parts, more preferably 4 to 6 parts, and more preferably 5 parts.

[0079] In the present invention, the type of the metal ion capture agent is not limited, and commercially available or non-commercially available products known to those skilled in the art can be used. Specifically in the embodiment, the manufacturer of the metal ion capture agent is Suzhou Shengyu Industry and Trade Co., Ltd.

[0080] In the present invention, the mass fraction of the metal ion scavenger is preferably 0.2 to 1 part, more preferably 0.5 to 1 part, and more preferably 0.5 part.

[0081] In the present invention, the stabilizer preferably includes one or more of hydroquinone, p-methoxyphenol, p-benzoquinone, 2,6-di-tert-butylcresol, and carbamate diol, and further preferably includes p-methoxyphenol, 2,6-di-tert-butylcresol or carbamate diol, and more preferably p-methoxyphenol or carbamate diol.

[0082] In the present invention, the weight percentage of the stabilizer is preferably 0.05 to 0.4 parts, more preferably 0.1 to 0.3 parts, and more preferably 0.2 parts.

[0083] The present invention also provides a method for preparing a semiconductor chip side encapsulation UV glue, comprising the following steps:

[0084] (1) mixing a first monomer, a second monomer, a third monomer, a fourth monomer and an initiator to carry out a polymerization reaction to obtain an acrylate copolymer;

[0085] (2) mixing and grinding the modified spherical silica, the negative thermal expansion material, the nano-silica, the fumed silica, the metal ion scavenger, the stabilizer and part of the acrylic ester copolymer, and controlling the fineness of the mixed grinding to be within 20 μm to obtain a first mixed material;

[0086] (3) vacuum mixing and vacuum grinding the epoxy resin, the remaining acrylate copolymer, the epoxy diluent and the first mixed material in sequence, and controlling the fineness of the vacuum grinding to be within 10 μm to obtain a second mixed material;

[0087] (4) The second mixed material and the photoinitiator are mixed at a temperature of less than 25° C., and vacuum filtered to control the particle size within 5 μm, thereby obtaining a semiconductor chip side encapsulation UV adhesive.

[0088] In the present invention, in step (1), the initiator preferably includes one or more of benzoyl peroxide, tert-butyl hydroperoxide, azobisisobutyronitrile, and azobisisoheptanenitrile, and further preferably includes benzoyl peroxide and / or azobisisobutyronitrile, and more preferably is benzoyl peroxide.

[0089] In the present invention, in step (1), the mass ratio of the first monomer to the initiator is preferably 1:0.05 to 0.3, more preferably 1:0.1 to 0.2, and more preferably 1:0.1.

[0090] In the present invention, in step (1), the conditions of the polymerization reaction include: the temperature is preferably 60-90°C, more preferably 75-90°C, more preferably 85°C; the time is preferably 6-12h, more preferably 8-10h, more preferably 8.5h.

[0091] In the present invention, in step (1), nitrogen is preferably introduced before the polymerization reaction.

[0092] In the present invention, the polymerization reaction in step (1) preferably specifically comprises the following steps:

[0093] The first monomer is heated, and the second monomer and part of the initiator are added thereto to react to obtain a first intermediate; the first intermediate, the third monomer and the remaining initiator are mixed and reacted to obtain a second intermediate; the second intermediate and the fourth monomer are mixed and reacted to obtain an acrylate copolymer.

[0094] In the present invention, the heating conditions include: the temperature is preferably 60-90°C, more preferably 75-90°C, and more preferably 85°C; the heating rate is preferably 1-5°C / min, more preferably 1-3°C / min, and more preferably 1°C / min.

[0095] In the present invention, the part of the initiator is preferably 20 to 50% of the total mass of the initiator, more preferably 30 to 45%, and even more preferably 40%.

[0096] In the present invention, the time for reacting the second monomer with part of the initiator is preferably 0.2 to 2 hours, more preferably 0.4 to 0.8 hours, and more preferably 0.5 hours.

[0097] In the present invention, the mixing reaction time is preferably 1 to 6 hours, more preferably 3 to 5 hours, and more preferably 4 hours.

[0098] In the present invention, the time for the mixing reaction of the second intermediate and the fourth monomer is preferably 1 to 6 hours, more preferably 3 to 5 hours, and even more preferably 4 hours.

[0099] In the present invention, the second monomer, part of the initiator, the third monomer, the remaining initiator and the fourth monomer are preferably added dropwise; the rate of the addition is independently preferably 4 to 10 mL / min, more preferably 4.5 to 6.5 mL / min, and more preferably 5 mL / min.

[0100] In the present invention, the portion of the acrylic ester copolymer in step (2) is preferably 20 to 50% of the total mass of the acrylic ester copolymer, more preferably 30 to 45%, and even more preferably 40%.

[0101] In the present invention, in step (2), the conditions for the mixed grinding are not limited, and the grinding can be performed until the fineness is within 20 μm.

[0102] In the present invention, in step (3), the conditions for the vacuum mixing are not limited, as long as the mixture is mixed evenly.

[0103] In the present invention, in step (3), the vacuum grinding conditions are not limited, and the grinding can be performed until the fineness is within 10 μm.

[0104] In the present invention, in step (4), the conditions for the vacuum filtration are not limited and any method familiar to those skilled in the art may be used.

[0105] In the present invention, the vacuum degrees of the vacuum mixing in step (3), the vacuum grinding in step (3) and the vacuum filtration in step (4) are independently preferably -0.07 to -0.5 MPa, more preferably -0.2 to -0.5 MPa, and even more preferably -0.4 MPa.

[0106] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0107] Example 1

[0108] The present embodiment provides a semiconductor chip side encapsulation UV glue, comprising the following raw materials in parts by mass: 15 parts of epoxy resin, 8 parts of acrylate copolymer, 60 parts of modified spherical silica, 5 parts of negative thermal expansion material, 12 parts of epoxy diluent, 5 parts of nano-silicon dioxide, 3 parts of fumed silica, 8 parts of photoinitiator, 0.5 parts of metal ion scavenger, and 0.2 parts of stabilizer;

[0109] Among the above raw materials, the epoxy resin is bisphenol A epoxy resin, CAS No.: 25036-25-3, and the manufacturer is Nippon Kayaku Chemical Co., Ltd.;

[0110] The preparation method of modified spherical silica comprises the following steps:

[0111] Spherical silica (2 μm) was first soaked in 0.5 mol / L sulfuric acid, then washed with deionized water until neutral, and then calcined at 400 °C for 3 h to obtain pretreated silica. The ethanol / water mixed solution (volume ratio 9:1) was adjusted to pH 5 with acetic acid, and epoxytriethoxysilane ( GLYEO) for 1 hour to obtain a silane solution with an epoxytriethoxysilane concentration of 12wt%; the pretreated silica was added to the above silane solution with a solid-liquid ratio of 1:10, and the temperature was controlled at 50°C for ultrasonic dispersion for 3 hours; then the crude product was separated at 5000rpm for 10 minutes using a centrifuge to obtain a crude product; the crude product was then washed with ethanol 3 times, dried at 80°C in a vacuum drying oven for 10 hours, and then heat treated at 110°C for 1.5 hours to obtain modified spherical silica;

[0112] The negative thermal expansion material is zirconium tungstate with a particle size of 1 μm;

[0113] The epoxy diluent is oxetane, CAS number: 503-30-0, and the manufacturer is Ube Chemical Co., Ltd. of Japan;

[0114] The particle size of nano-silicon dioxide is 20 nm, and the manufacturer is Nippon Denka Co., Ltd.;

[0115] The particle size of fumed silica is <10nm, and the manufacturer is Wacker Chemical of Germany;

[0116] The photoinitiator is 2 parts of castor oil polyol ( T-400, Vantros Specialty Products, Inc., USA), 3 parts of 3,4-dihydroxy-3-cyclobutene-1,2-dione, 3 parts of photoinitiator 184;

[0117] The metal ion capture agent is a heavy metal ion capture agent sold by Suzhou Shengyu Industry and Trade Co., Ltd.;

[0118] The stabilizer is p-methoxyphenol.

[0119] This embodiment also provides a method for preparing the above-mentioned UV glue, comprising the following steps:

[0120] (1) nitrogen is passed through a reactor to replace the air therein, butyl acrylate is added, the temperature is raised from room temperature to 85°C at a rate of 1°C / min, a mixture of acrylonitrile and 40 wt% initiator benzoyl peroxide is added dropwise at a rate of 6 mL / min, and the mixture is refluxed for 0.5 h after the addition is completed to obtain a first intermediate; a mixture of dicyclopentadiene acrylate (model DCPA, manufactured by Hitachi Chemical Co., Ltd.) and the remaining initiator benzoyl peroxide is added dropwise at a rate of 6 mL / min to the first intermediate, and the mixture is refluxed for 4 h after the addition is completed to obtain a second intermediate; glycidyl methacrylate is added dropwise at a rate of 6 mL / min to the second intermediate, and the mixture is refluxed for 4 h after the addition is completed, the mass ratio of butyl acrylate, acrylonitrile, dicyclopentadiene acrylate and glycidyl methacrylate is 5:0.5:1.5:3, and the mass ratio of butyl acrylate to initiator is 1:0.1. After the reaction is completed, the mixture is filtered, washed, and vacuum dried to obtain an acrylate copolymer;

[0121] (2) mixing and grinding the modified spherical silica, the negative thermal expansion material, the nano-silica, the fumed silica, the metal ion scavenger, the stabilizer and 40 wt % of the acrylic acid ester copolymer to control the fineness to be within 20 μm to obtain a first mixed material;

[0122] (3) mixing the epoxy resin, the remaining amount of the acrylic copolymer, the epoxy diluent and the first mixed material uniformly under a vacuum degree of -0.4 MPa, and then grinding them under the vacuum degree to a fineness of less than 10 μm to obtain a second mixed material;

[0123] (4) The second mixed material and the photoinitiator are mixed at 15° C., and filtered under a vacuum degree of -0.4 MPa to control the particle size within 5 μm, thereby obtaining a semiconductor chip side encapsulation UV glue.

[0124] Example 2

[0125] The present embodiment provides a semiconductor chip side encapsulation UV glue, comprising the following raw materials in parts by mass: 20 parts of epoxy resin, 18 parts of acrylate copolymer, 32 parts of modified spherical silica, 6 parts of negative thermal expansion material, 8 parts of epoxy diluent, 6 parts of nano silica, 3 parts of fumed silica, 6 parts of photoinitiator, 0.5 parts of metal ion scavenger, and 0.2 parts of stabilizer; the photoinitiator is 2 parts of castor oil polyol, 2 parts of 3,4-dihydroxy-3-cyclobutene-1,2-dione, and 2 parts of photoinitiator 184; other parameter conditions are the same as those in Example 1.

[0126] Comparative Example 1

[0127] The difference between this comparative example and Example 1 is that castor oil polyol and 3,4-dihydroxy-3-cyclobutene-1,2-dione are deleted, and other parameter conditions are the same as those in Example 1.

[0128] Comparative Example 2

[0129] The difference between this comparative example and Example 1 is that the acrylic acid ester copolymer is deleted, and other parameter conditions are the same as those in Example 1.

[0130] Comparative Example 3

[0131] The difference between this comparative example and Example 1 is that the negative thermal expansion material is deleted, and other parameter conditions are the same as those of Example 1.

[0132] Comparative Example 4

[0133] The difference between this comparative example and Example 1 is that the modified spherical silica is deleted, and other parameter conditions are the same as those in Example 1.

[0134] Comparative Example 5

[0135] The difference between this comparative example and Example 1 is that the modified spherical silica is replaced by spherical silica, and the other parameter conditions are the same as those in Example 1.

[0136] The performance tests were conducted on the UV glue obtained in Examples 1 to 2 and Comparative Examples 1 to 5. Among them, the glass transition temperature and the coefficient of thermal expansion were tested with reference to IPC-TM-650; the volume resistivity and the surface resistivity were tested with reference to ASTM D257; the thixotropic coefficient was tested using a rotational viscometer; the shear strength was tested with reference to ASTM D1002; the bonding strength was tested with reference to ASTM-D-1002; the hardness after curing was tested using a Shore D durometer; the test method for the curing depth was: using LED 365nm wavelength ultraviolet light to test the curing depth of the UV glue under the light curing condition of 9000mJ / 10s; the test method for the reworkability was: after the UV glue was cured, the cured glue strip was heated, and the temperature when the glue strip became brittle and did not damage the green oil and the pad was recorded; the solvent resistance was tested with reference to IPC-TM-650; the hydrolysis stability was tested with reference to SJT11187; and the solder paste compatibility was tested with reference to IPC-TM650. The results of the performance tests are shown in Table 1.

[0137] Table 1. Test results of UV adhesive performance obtained in Examples 1 to 2 and Comparative Examples 1 to 5

[0138]

[0139]

[0140] As can be seen from Table 1, after deleting castor oil polyol and 3,4-dihydroxy-3-cyclobutene-1,2-dione, the curing depth of Comparative Example 1 was significantly reduced, proving that the use of a mixed system of photocuring agents is more conducive to improving the curing depth. After deleting the acrylate copolymer in Comparative Example 2, its rework performance, solvent resistance, and solder paste compatibility deteriorated, and the glass transition temperature increased, indicating that the acrylate copolymer has thermal reversibility, making the rework operation easier and improving solvent resistance. After deleting the negative thermal expansion material in Comparative Example 3, its thermal expansion coefficient was significantly improved, and the curing depth decreased, indicating that the negative thermal expansion material can effectively reduce the CTE value. After deleting the modified spherical silica in Comparative Example 4, its thermal expansion coefficient was greatly improved, indicating that the modified spherical silica can synergistically reduce the CTE value with the negative thermal expansion material. In Comparative Example 5, under the condition that the spherical silica was not modified, the UV curing depth was significantly reduced, indicating that modifying the spherical silica can effectively improve the light transmittance. Therefore, the components in the present application are indispensable and can synergistically improve the various performance properties of the UV glue.

[0141] Example 3

[0142] The present embodiment provides a semiconductor chip side encapsulation UV glue, comprising the following raw materials in parts by weight: 12 parts of epoxy resin, 15 parts of acrylate copolymer, 50 parts of modified spherical silica, 5 parts of negative thermal expansion material, 10 parts of epoxy diluent, 5 parts of nano-silicon dioxide, 2 parts of fumed silica, 5 parts of photoinitiator, 0.2 parts of metal ion scavenger, and 0.1 parts of stabilizer;

[0143] Among the above raw materials, the epoxy resin is bisphenol F epoxy resin, CAS No.: 028064-14-4, and the manufacturer is Nippon Kayaku Chemical Co., Ltd.;

[0144] The preparation method of modified spherical silica comprises the following steps:

[0145] Spherical silica (1 μm) was first soaked in 1 mol / L sulfuric acid, then washed with deionized water until neutral, and then calcined at 400 °C for 4 h to obtain pretreated silica. The ethanol / water mixed solution (volume ratio 10:1) was adjusted to pH 4 with acetic acid, and epoxytriethoxysilane ( GLYEO) for 2 hours to obtain a silane solution with an epoxytriethoxysilane concentration of 15wt%; the pretreated silica was added to the above silane solution with a solid-liquid ratio of 1:10, and the temperature was controlled at 60°C for ultrasonic dispersion for 2.5 hours; then the crude product was separated at 4000rpm for 10 minutes using a centrifuge to obtain a crude product; the crude product was then washed with ethanol for 3 times, dried at 60°C in a vacuum drying oven for 12 hours, and then heat treated at 120°C for 1 hour to obtain modified spherical silica;

[0146] The negative thermal expansion material is β-eucryptite with a particle size of 800nm;

[0147] The epoxy diluent is vinyl ethyl ether;

[0148] The particle size of nano-silicon dioxide is 20 nm, and the manufacturer is Nippon Denka Co., Ltd.;

[0149] The particle size of fumed silica is <10nm, and the manufacturer is Wacker Chemical of Germany;

[0150] The photoinitiator is 2 parts of castor oil polyol ( T-400, Vantros Specialty Products, Inc., USA), 1 part 3,4-dihydroxy-3-cyclobutene-1,2-dione, 2 parts isopropylthioxanthone ITX;

[0151] The metal ion capture agent is a heavy metal ion capture agent sold by Suzhou Shengyu Industry and Trade Co., Ltd.;

[0152] The stabilizer is 2,6-di-tert-butylcresol.

[0153] This embodiment also provides a method for preparing the above-mentioned UV glue, comprising the following steps:

[0154] (1) nitrogen is passed through a reactor to replace the air therein, ethyl acrylate is added, the temperature is raised from room temperature to 85°C at a rate of 1°C / min, a mixed solution of styrene and 40 wt% initiator azobisisobutyronitrile is added thereto at a rate of 5 mL / min, and the mixture is refluxed for 0.5 h after the addition is completed to obtain a first intermediate; a mixed solution of isobornyl methacrylate and the remaining initiator azobisisobutyronitrile is added to the first intermediate at a rate of 5 mL / min, and the mixture is refluxed for 4 h after the addition is completed to obtain a second intermediate; glycidyl methacrylate is added to the second intermediate at a rate of 5 mL / min, and the mixture is refluxed for 4 h after the addition is completed, the mass ratio of ethyl acrylate, styrene, isobornyl methacrylate and glycidyl methacrylate is 5:0.5:1.5:3, and the mass ratio of ethyl acrylate to initiator is 1:0.1. After the reaction is completed, the mixture is filtered, washed, and vacuum dried to obtain an acrylate copolymer;

[0155] (2) mixing and grinding the modified spherical silica, the negative thermal expansion material, the nano-silica, the fumed silica, the metal ion scavenger, the stabilizer and 40 wt % of the acrylic acid ester copolymer to control the fineness to be within 20 μm to obtain a first mixed material;

[0156] (3) mixing the epoxy resin, the remaining amount of the acrylic copolymer, the epoxy diluent and the first mixed material uniformly under a vacuum degree of -0.4 MPa, and then grinding them under the vacuum degree to a fineness of less than 10 μm to obtain a second mixed material;

[0157] (4) The second mixed material and the photoinitiator are mixed at 15° C., and filtered under a vacuum degree of -0.4 MPa to control the particle size within 5 μm, thereby obtaining a semiconductor chip side encapsulation UV glue.

[0158] Example 4

[0159] The present embodiment provides a semiconductor chip side encapsulation UV glue, comprising the following raw materials in parts by mass: 15 parts of epoxy resin, 25 parts of acrylate copolymer, 40 parts of modified spherical silica, 10 parts of negative thermal expansion material, 5 parts of epoxy diluent, 10 parts of nano-silicon dioxide, 5 parts of fumed silica, 3 parts of photoinitiator, 1 part of metal ion scavenger, and 0.5 parts of stabilizer; the photoinitiator is 1 part of castor oil polyol, 1 part of 3,4-dihydroxy-3-cyclobutene-1,2-dione, and 1 part of isopropylthioxanthone ITX; other parameter conditions are the same as those in Example 3.

[0160] In summary, it is not difficult to find from the test results of the above embodiments that the side encapsulation UV glue prepared in the present application has excellent performance, which makes the side filling have the following advantages:

[0161] (1) More cost-effective: During the side filling process, there is no need to completely fill the space between the BGA and the PCB with resin as in the bottom filling process. The reduction in the amount of resin used directly reduces the material cost. At the same time, the filling operation is relatively simple and fast, which can save a lot of time cost in the mass production process, so the cost is lower.

[0162] (2) Lighter weight: For some weight-sensitive devices, side filling can reduce the weight burden to the greatest extent. This is because side filling only requires adding resin on three sides, which adds less weight than bottom filling, which completely fills the entire space. This advantage is particularly important in fields such as aerospace and wearable devices that have strict weight requirements.

[0163] (3) Reduce bubble problems: Bottom filling increases the risk of bubbles when filling the entire space between the BGA and the PCB. These bubbles may affect the filling effect and reduce the reliability of the connection, and the expansion and contraction of the bubbles during thermal cycling may cause additional stress on the solder joints. Side filling only adds resin on three sides, effectively avoiding this problem and making the module performance more stable.

[0164] (4) Enhanced connection stability: By filling the three sides of the DRAM IC with the UV glue of the present application, the connection between the PCB and the ball grid array (BGA) can be effectively strengthened. This provides additional support for the overall structure when the BGA size becomes smaller and the stability of the solder joints decreases, reducing the looseness or damage of the connection caused by mechanical stress (such as impact and vibration).

[0165] (5) Electrical performance: Side filling with UV glue can reduce the contact between the solder joint and the air, reduce the risk of electrical performance degradation due to factors such as oxidation, and help maintain the conductivity and stability of the solder joint, thereby ensuring the quality of signal transmission.

[0166] (6) Local reinforcement is highly targeted: It is mainly used to reinforce the side parts of the module, which is very effective for situations where the force is concentrated in a specific direction. For example, when the equipment may be hit from the side during transportation or there is a lateral vibration source in the use environment, the side filling can effectively resist these lateral forces and protect the BGA and solder joints.

[0167] (7) Friendly to ultra-miniaturized and ultra-large modules: The side-filled UV glue does not take up too much space and can adapt to the trend of the module's size being continuously reduced or enlarged, thus improving its stability without significantly increasing the module's volume.

[0168] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A semiconductor chip side encapsulation UV glue, characterized in that: The invention comprises the following raw materials in parts by weight: 10 to 20 parts of epoxy resin, 5 to 30 parts of acrylate copolymer, 30 to 80 parts of modified spherical silica, 5 to 10 parts of negative thermal expansion material, 5 to 15 parts of epoxy diluent, 5 to 10 parts of nano silica, 1 to 5 parts of fumed silica, 1 to 10 parts of photoinitiator, 0.1 to 2 parts of metal ion scavenger and 0 to 0.5 parts of stabilizer.

2. The semiconductor chip side encapsulation UV glue according to claim 1, characterized in that: The epoxy resin includes one or more of silicone alicyclic epoxy resin, alicyclic epoxy resin, bisphenol A epoxy resin, and bisphenol F epoxy resin.

3. The semiconductor chip side encapsulation UV glue according to claim 1, characterized in that: The acrylic ester copolymer is prepared by copolymerizing a first monomer, a second monomer, a third monomer and a fourth monomer; The first monomer includes one or more of allyl acrylate, ethyl acrylate, butyl acrylate, isooctyl acrylate, ethyl methacrylate, allyl methacrylate, butyl methacrylate, and hydroxyethyl methacrylate; The second monomer includes one or more of acrylic acid, methacrylic acid, acrylonitrile, styrene, 1,3-butadiene, acrylamide, and α-methylstyrene; The third monomer includes one or more of dicyclopentadiene acrylate, isobornyl methacrylate, isobornyl acrylate, 2-phenoxyethyl acrylate, and 1,6-hexanediol diacrylate; The fourth monomer includes one or more of glycidyl acrylate, glycidyl methacrylate, 2,3-epoxybutyl acrylate, allyl glycidyl ether, butyl glycidyl ether, and phenyl glycidyl ether; The mass ratio of the first monomer, the second monomer, the third monomer and the fourth monomer is 5-8:0.5-2:1-1.5:1-3.

4. The semiconductor chip side encapsulation UV glue according to claim 1, characterized in that: The negative thermal expansion material includes zirconium tungstate and / or β-eucryptite; The particle size of the negative thermal expansion material is 500nm-1μm.

5. The semiconductor chip side encapsulation UV glue according to claim 1, characterized in that: The epoxy diluent includes one or more of oxetane, vinyl ether, and allyl ether.

6. The semiconductor chip side encapsulation UV glue according to claim 1, characterized in that: The modified spherical silica is prepared by modifying spherical silica with a silane coupling agent, and the particle size of the spherical silica is 0.5 to 5 μm; The particle size of the nano silicon dioxide is 10 to 20 nm; The particle size of the fumed silica is less than 10 nm.

7. The semiconductor chip side encapsulation UV glue according to claim 1, characterized in that: The photoinitiator comprises a mixture of a first component and a second component; The first component includes a mixture of castor oil polyol and 3,4-dihydroxy-3-cyclobutene-1,2-dione; The second component includes one or more of the photoinitiator 184, isopropylthioxanthone ITX, sulfonium phosphate, iodonium phosphate, sulfonium antimonate ammonium salt, aziridine acrylate, and acridine.

8. The semiconductor chip side encapsulation UV glue according to claim 1, characterized in that: The stabilizer includes one or more of hydroquinone, p-methoxyphenol, p-benzoquinone, 2,6-di-tert-butyltoluene, and carbamate diol.

9. The method for preparing a semiconductor chip side encapsulation UV glue according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) mixing a first monomer, a second monomer, a third monomer, a fourth monomer and an initiator to carry out a polymerization reaction to obtain an acrylate copolymer; (2) mixing and grinding the modified spherical silica, the negative thermal expansion material, the nano-silica, the fumed silica, the metal ion scavenger, the stabilizer and part of the acrylic ester copolymer, and controlling the fineness of the mixed grinding to be within 20 μm to obtain a first mixed material; (3) vacuum mixing and vacuum grinding the epoxy resin, the remaining acrylate copolymer, the epoxy diluent and the first mixed material in sequence, and controlling the fineness of the vacuum grinding to be within 10 μm to obtain a second mixed material; (4) The second mixed material and the photoinitiator are mixed at a temperature of less than 25° C., and vacuum filtered to control the particle size within 5 μm, thereby obtaining a semiconductor chip side encapsulation UV adhesive.

10. The preparation method according to claim 9, characterized in that: The polymerization reaction in step (1) specifically comprises the following steps: The first monomer is heated, and the second monomer and part of the initiator are added thereto to react to obtain a first intermediate; the first intermediate, the third monomer and the remaining initiator are mixed and reacted to obtain a second intermediate; the second intermediate and the fourth monomer are mixed and reacted to obtain an acrylate copolymer.